(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The Brazilian scientific community in Psychology has grown, in the last decades, in the number of researchers, as well as in research subareas, graduate programs, and in organizational and representational processses. Behavior analysis faced, in the same period, a notable advancement, largely promoted by events and publications by the Brazilian Association for Psychotherapy and Behavioral Medicine. Such a progress, however, has not been one in the field of organization and representation of the Brazilian scientific community in behavior analysis, which remains a challenge.